Genetic Dissection of the Kluyveromyces lactis Telomere and Evidence for Telomere Capping Defects in TER1 Mutants with Long Telomeres - Underwood, Dana H. (American Society for Microbiology, 2004)
In the yeast Kluyveromyces lactis, the telomeres are composed of perfect 25-bp repeats copied from a 30-nucleotide RNA template defined by 5-nucleotide terminal repeats. A genetic dissection of the K. lactis telomere was performed by using mutant telomerase RNA (TER1) alleles to incorporate mutated telomeric repeats. This analysis has shown that each telomeric repeat contains several functional regions, some of which may physically overlap. Mutations in the terminal repeats of the template RNA typically lead to telomere shortening, as do mutations in the right side of the Rap1p binding site. Mutations in the left half of the Rap1p binding site, however, lead to the immediate formation of long telomeres. When mutated, the region immediately 3′ of the Rap1p binding site on the TG-rich strand of the telomere leads to telomeres that are initially short but eventually undergo extreme telomere elongation. Mutations between this region and the 3′ terminal repeat cause elevated recombination despite the presence of telomeres of nearly wild-type length. Mutants with highly elongated telomeres were further characterized and exhibit signs of telomere capping defects, including elevated levels of subtelomeric recombination and the formation of extrachromosomal and single-stranded telomeric DNA. Lengthening caused by some Rap1 binding site mutations can be suppressed by high-copy-number RAP1. Mutated telomeric repeats from a delayed elongation mutant are shown to be defective at regulating telomere length in cells with wild-type telomerase, indicating that the telomeric repeats are defective at telomere length regulation.